Digital economy and green development: Empirical evidence from China’s cities - Xiao, Yue; Wu, Si; Liu, Zai Qi; Lin, Hai Ji (Frontiers in Environmental Science, 2023)
With prominent environmental pollution and depleted resources, how to coordinate economic growth and eco-environmental protection to guide green development represented by green total factor productivity (GTFP) is an urgent issue. This study aims to empirically evaluate the direct effect, indirect effect, spatial spillover effect and nonlinear effect of the digital economy on green development using the data of 284 prefecture-level cities in China. The empirical results indicate that: (1) the digital economy significantly improves GTFP, which is still valid after testing for robustness, including introducing instrumental variables, taking the “broadband China” pilot policy as a quasi-natural experiment, changing core explanatory variables and dependent variables, and changing the sample size; (2) the influence of the digital economy on GTFP is characterized by significant heterogeneity among resource dependence, geographical location, financial development level and openness level; (3) the mechanism analysis shows that the digital economy promotes GTFP by green technological innovation, industrial structure upgrading and energy conservation; (4) the spatial econometric models indicate that the digital economy significantly enhances GTFP of neighboring cities; (5) there is a nonlinear relationship between the digital economy and GTFP using the threshold model. The findings could provide references for policymakers to promote urban green development.